First data on the Evolution duodenal stent for palliation of malignant gastric outlet obstruction (DUOLUTION study): a prospective multicenter study - van den Berg, M. W.; Haijtink, S.; Fockens, P.; Vleggaar, F. P.; Dijkgraaf, M. G. W.; Siersema, P. D.; van Hooft, J. E. (Endoscopy, 2013)
Background and study aims: Enteral stent placement has emerged as a safe and effective palliative treatment option for patients with malignant gastric outlet obstruction (GOO). In an attempt to further optimize this treatment new enteral stents have been designed. This study is the first to describe the results regarding technical success, clinical success, complication rate, and stent dysfunction of the Evolution duodenal stent (Cook Medical, Limerick, Ireland). Patients and methods: A total of 46 patients with symptomatic malignant GOO were included in this prospective multicenter cohort study. All patients who successfully received an Evolution duodenal stent were followed until death. Results: The technical and clinical success rates were 89 % (95 % confidence interval [CI] 77 % – 95 %) and 72 % (95 %CI 58 % – 83 %), respectively. The GOO Scoring System score, the Global Health Score, and the EuroQol visual analog scale improved significantly (GOOSS and Global Health Score P < 0.0001; EuroQol P = 0.005) when scores before stenting were compared with scores after stent placement. Median survival was 87 days, and stent patency was observed in 67 % for up to 395 days, accounting for death unrelated to the stent as a competing risk. Stent dysfunction occurred in 14 patients (30 %) (stent ingrowth n = 9; stent migration n = 2; extrinsic compression on the stent n = 2; food impaction n = 1). Conclusion: These first data on the new Evolution duodenal stent show that it is safe and effective for the palliative treatment of symptomatic malignant GOO.